Accessory lower limb associated with spina bifida: case report - DAĞÇINAR, ADNAN; BAYRİ, YAŞAR (SPRINGER, 2014)
Heterotopic redundancies, such as an accessory limb associated with spina bifida, are extremely rare anomalies. There are 12 cases of accessory limb associated with spinal bifida in literature. This report aims a detailed description of the additional case and an analysis of the findings in light. A male baby was born at 40 weeks of gestation and was referred to the neurosurgery clinic with a diagnosis of accessory lower limb. On physical examination, the dorsal meningocele was located at the lumbosacral region and there was accessory lower limb on it. There was no open neural placode. The accessory limb was excised on postnatal day 3. Dysraphic appendages are rare and complicated anomalies. They should be investigated carefully, and all of the lesions must be repaired for babies' quality of life.
Keywords: Accessory limb; Spina bifida; Heterotopic redundancy; Dysraphic appendage; DYSRAPHISM